Characterising the HIV self-testing market in Kenya: Awareness and usage, barriers and motivators to uptake, and propensity to pay. - Rebecca L West; Lily Freeman; Charlotte Pahe; Harmon Momanyi; Catherine Kidiga; Serah Malaba; Joanna Ciecielag; Mary-Clare Ridge; Emma Goldwin; Heather Awsumb; Sunny Sharma (Public Library of Science (PLoS), 2023)
HIVST has a key role in ensuring countries meet their 95-95-95 goals. For HIVST to be sustainable, we should explore sharing costs with users as well as the overall experience. This research explores why a consumer would use HIVST and willingness to pay for HIVST through surveying 1,021 participants 18-35 living in Nairobi or Kisumu who were not diagnosed as HIV positive and who are not currently taking PrEP for HIV. A majority (89.8%) would pay 100 KSH and 64.7% would pay 300 KSH, at higher prices likelihood of paying dropped sharply. Price reduction or subsidization coupled with interventions to address the identified barriers may increase HIVST uptake. We identified 5 distinct groups based on willingness to pay and drivers/ barriers to HIVST uptake. These were created using dimension reduction, hierarchical clustering, and k-means analysis to group respondents. 79% of participants had ever heard of HIVST, and 24% had ever used HIVST. The 5 groups included active users, unlikely users, and three segments interested in HIVST with different barriers: need for HCP support, need for increased privacy/confidentiality, and fear of positive result/disclosure.